Adaptacion Argentina de la entrevisia Manheim de apoyo social - Sacchi, Carla; Richaud de Minzi, Maria Cristina (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Our aim in this study was to analyze the psychometric characteristics of the Manheim Interview of Social Support (MISS) in Argentina. The adapted version of the MISS was administered to a sample of 198 Argentine participants. The local version of the MISS exhibited a stable configuration. We corroborated that, the inclusion of the kin/nonkin dimension was supported. Finally, low correlations with the Beck Depression Inventory and the UCLA Loneliness Scale suggest the convenience of a complementary evaluation of the subjective and cognitive aspects of support if one were to predict variables associated with health and illness. In conclusion, the MISS provides a complete description of the social network and its functions, which is important for prevention and intervention programs.